Strategic Investment Resilience: Navigating Economic Recession Risks through Diversification and Innovation - Judijanto, Loso; Liestyowati, Liestyowati; Kamaroellah, Agoes; Tawil, Muhamad Risal; Kamar, Karnawi; Ridwan, Mohammad (Journal of Ecohumanism, 2025)
The worldwide economic decline caused by the COVID-19 pandemic has highlighted the necessity for strategic investment resilience within enterprises. This research examines the relationship between diversity and innovation as essential methods for managing economic recessions. The study used a mixed-methods approach, including quantitative surveys of management-level participants and qualitative interviews with essential stakeholders from various industries. Research indicates that firms using diversification—across goods, markets, and geographies—coupled with creative practices, markedly improve their resilience during economic recessions. The research emphasizes the significance of proactive strategy frameworks that promote flexibility and adaptation, ultimately assisting organizations in attaining sustainable success amid uncertainty. Policymakers are urged to cultivate conditions that promote resilience-building investments instead of depending solely on foreign aid. This study enhances the academic discussion on strategic management by amalgamating risk management theory with innovation and investment strategies, providing pragmatic insights for firms facing economic difficulties.